1994
DOI: 10.1093/oxfordjournals.eurheartj.a060446
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma endothelin concentrations in heart failure; an effect of angiotensin II?

Abstract: Endothelin is a powerful vasoconstrictor that may be partly responsible for the increases in venous and arterial tone characteristic of heart failure. The release of endothelin from endothelial cells in culture is stimulated by angiotensin II. We investigated the relationship between plasma concentrations of immuno reactive endothelin-1 and angiotensin II in 25 patients with heart failure and eight with ischaemic heart disease but normal left ventricular function. Plasma concentrations of endothelin and angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Evidence shows that the RAS is activated during ischemia and reperfusion, with the Ang II peptide being one of the main causes of the cardiac damage. [21][22][23] Reperfusion arrhythmias are associated with changes in Ca +2 levels and it is well established that Ang II not only stimulates Ca +2 influx through Ca +2 channels but also induces release of intracellular Ca +2 , resulting in excess of Ca +2 inside the cells during ischemia/ reperfusion injury. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that the RAS is activated during ischemia and reperfusion, with the Ang II peptide being one of the main causes of the cardiac damage. [21][22][23] Reperfusion arrhythmias are associated with changes in Ca +2 levels and it is well established that Ang II not only stimulates Ca +2 influx through Ca +2 channels but also induces release of intracellular Ca +2 , resulting in excess of Ca +2 inside the cells during ischemia/ reperfusion injury. 8 …”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in the role of pulmonary hypertension and right heart dysfunction in patients with heart failure, which seem to be better guides to prognosis than left ventricular dysfunction (Damy et al, 2010). Plasma ET is more closely related to pulmonary vascular resistance than other hemodynamic features of heart failure and this relationship may be causal (Cody et al, 1992;Givertz et al, 2000;Good et al, 1994;Ooi et al, 2002). Thus, ET could be an important driver of this pathway of progression of heart failure.…”
Section: Endothelin In Heart Failurementioning
confidence: 99%
“…In addition, several studies have reported that angiotensin II stimulates production of reactive oxygen species (ROS)in vascular smooth muscle cells via NADH/NADPH oxidase activation [13,14]. It has been proposed that angiotensin II levels are elevated in ischemic heart disease [15,16], liver injury [17], cerebral ischemia [18] and renal injury [19]. Furthermore, angiotensin I-converting enzyme inhibition, which decreases the production of angiotensin II, has been shown to improve postischemic injury in both animal and human studies [20,21].…”
Section: Introductionmentioning
confidence: 99%